2009
DOI: 10.1111/j.1468-5906.2009.01463.x
|View full text |Cite
|
Sign up to set email alerts
|

Higher Education as Moral Community: Institutional Influences on Religious Participation During College

Abstract: Borrowing from the literature on religion and deviance, the concept of moral communities is applied to religious and secular postsecondary education to explain institutional influences on student religious participation. Results from nationally representative panel data indicate that students attending Catholic and mainline Protestant affiliated institutions decline in religious participation at a faster rate than students attending evangelical institutions or students attending nonreligious public colleges an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
98
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(111 citation statements)
references
References 27 publications
11
98
1
1
Order By: Relevance
“…But this study's findings have implications for other religious beliefs, moral schemas, religious practices, and resources. Recent work has complicated our understanding of individual educational attainments' effects on religious outcomes (Uecker et al, 2007) as well as the effects of secular and religious educational contexts (Barrett et al, 2007;Hill, 2009). Congregational educational attainment and its interplay with personal education should also be explored in connection with various other religious forms, expressions, and consequences.…”
Section: Discussionmentioning
confidence: 99%
“…But this study's findings have implications for other religious beliefs, moral schemas, religious practices, and resources. Recent work has complicated our understanding of individual educational attainments' effects on religious outcomes (Uecker et al, 2007) as well as the effects of secular and religious educational contexts (Barrett et al, 2007;Hill, 2009). Congregational educational attainment and its interplay with personal education should also be explored in connection with various other religious forms, expressions, and consequences.…”
Section: Discussionmentioning
confidence: 99%
“…Research has demonstrated that the college experiences, particularly liberal arts experiences typical of honors programs, challenged previously held beliefs (Bryant, 2011;Hébert & McBee, 2007). In contrast, other studies revealed that faith-based institutions created social and academic environments that reinforced the beliefs and practices of the enrolled students (Hill, 2009). Even though some change was expected because of the maturation process (Arnett, 2011), exploring the experiences of honors students and their reflections on those experiences contributed valuable insights into the college developmental process.…”
Section: Methodsmentioning
confidence: 99%
“…As part of this exploration, Arnett notes that emerging adults engage in the highest levels of risk behaviors of any time in the life span. Also during this time of exploration, most American university students report a stability, if not strengthening of their religious beliefs since the start of college (Lefkowitz 2005;Stoppa and Lefkowitz 2010), but their participation in religious activities declines over this time period (Hill 2009). Religiosity has long been found to buffer the engagement in risk behaviors (e.g., Wells 2010), so there may be a complex association between religiosity and risk behavior during emerging adulthood.…”
mentioning
confidence: 97%